Instituições participativas: audiências públicas para revisão do plano diretor no município de Araraquara - Lopes, Maira Gonçalves (Universidade Federal de São Carlos, 2014)
On the traversed course through the literature about institutional participation, it is possible to point distinct moments to deal with. In this dissertation was recovered the discussion approached by Carlos Estevam Martins, that in the end of the eighties and begin of nineties, bring forward the participation theme into the theory of the State and highlighted the relationship of participation and representation in this context. Following, we brought to the debate inspired research by the Habermasian theory, that pointed to an enthusiasm with the new forms of institutional participation. Subsenquently, research showed that was a large disparity between empiric bases and normative expectations in the literature until then. The last and current moment, focuses its efforts to the effective question of participation. During this period, many participation institutions (PIs) was analyzed and evaluated, however, the research about Public Hearings was rare. Based in the literature balance, this dissertation proposed to analyze Public Hearings, in the municipality of Araraquara-SP( Brazil), that was made throughout the revision process of the Master Plan of this city in 2013. The research point that the hearings, because of yours advisory character, worked as debate environments, but not as a political instrument of propositions and decisions. In addition, this Public Hearings operate as a subordinate participation instrument of government authority, because is that one who is able to incorporate or reject submitted suggestions by the population in this environment.
Keywords: Participação política; Instituições participativas; Participação política; Audiências públicas; Participatory; Participatory institutions; Public hearings; CIENCIAS HUMANAS::CIENCIA POLITICA